Mobile RFID system authentication protocol based on one-way pseudo random function - Biyuan JIAN; Daowei LIU (Dianxin kexue)
Aiming at the cost,efficiency and security of mobile RFID system authentication,a mobile RFID authentication protocol based on one-way pseudo random function was designed.The protocol reduced system cost by making full use of the three party of the shared key and communication information to encrypt transmission and authentication.Through the implementation of three party authentication and key update work,the agreement suffered counterfeit,desynchronization and other attacks was avoided.Finally,the logical proof of GNY and its security and performance analysis were gived to show the feasibility and security of the new protocol.